ANALISIS PENERAPAN APLIKASI INSPEKSI VISUAL JEMBATAN INVI J (USER PERSPECTIVE) - Putri, Citra Kharisma; Sastrawiria, Risma Putra Pratama (Civil Infrastructure Engineering and Architectural Design, 2018)
Research and Development Agency for Road and Bridge Ministry of Public Works and Public Housing (Balitbang Pusjatan Kemen-PUPR) has developed a bridge inspection software called Visual Inspection of Bridge or INVI J. The INVI J application which based on Android software and web has been implemented starting in 2018 at all Balai Besar Pelaksanaan Jalan Nasional (BBPJN) throughout Indonesia. Related to that, the analysis of user perspective towards the utilization of the INVI J is significant to be done.This research was conducted by creating and distributing questionnaires to several INVI J software users within the Balai Besar Pelaksanaan Jalan Nasional (BBPJN), Satuan Kerja (Satker), Pejabat Pembuat Komitmen (PPK) and Consultant.From this study, it can be concluded that in general the INVI J software is easy to learn, easy to operate and useful for users in conducting bridge surveys because it is faster than filling out a manual inspection form. However, INVI J does not have the ability and function as expected and the output produced is still not as desired, hence it is necessary to make an updating the application, in order optimize the output.